PEMBELAJARAN EMBRIOGENESIS MEMPERKUAT PENDIDIKAN KARAKTER DIRI SISWA SMP/MTs MASA PUBERTAS - Yuswa Istikomayanti; Anis Trianawati (Universitas Tribhuwana Tunggadewi, 2020)
This study aims to provide learning to puberty students from the results of validated learning designs. Through embryogenesis material that takes precedence with knowledge and is strengthened by a religious approach that further strengthens the character of puberty students to manifest themselves. This study uses a phenomenological approach through learning observations and student and teacher interviews to describe how the learning process occurs. Student data responses in learning and teacher responses obtained through interviews and observer field notes were then analyzed with the research team to be presented. Through the science and religion approach students become more open and aware of their life origins, respect themselves and their families. The teacher also stated that his hesitation in delivering this material was resolved by this method. Through the approach of religion and scientific facts for the age of puberty students, learning becomes more contextual and strengthen the character of adolescent students.